ERROR ANALYSIS OF DOOSHI USAGE IN THE COLLAGE STUDENT’S ESSAY OF THE JAPANESE LANGUAGE EDUCATION STUDY PROGRAM UNNES IN THE SAKUBUN CHUKYU ZENHAN’S SUBJECT - Aditya Hendra Cahya; Silvia Nurhayati; Yuyun Rosliyah (Universitas Negeri Semarang, 2018)
Abstract ___________________________________________________________________ Based on interview to a lecture of SakubunChukyuZenhan’s subjectin preliminary studythat has been conducted, showed that errors are often experienced by collegers of Japanese Language Education Program UNNES in writing sakubun(essay). Based on the results of the preliminary study questionnaire to 20 students of the fourth semester who took the subject of Sakubun Chukyu Zenhan showed that 70% of students is having difficulty in using of verbs (dooshi) . Therefore, researcher want to analyze anyerror of the students in the usege of dooshi in Sakubun Chukyu Zenhan's subject. Data collection methods used in this research issentence fragment of the student's essay of the fourth semester of Japanese Language Education Program of State University of Semarang which is considered of less precise in the dooshi’s usage.Theamount of the data is 25 essay sthemed konbini no ankeeto of the second study group of Sakubun Chukyu Zenhan’s subjec. The approachment of this research is descriptive quantitative analysis. Following conclusions are obtained based on the results of the research. Based on the results of the research found that there are 83 errors in the usege of dooshi. The errors is consisting of 64 or 77% errors are in the verb changes (dooshi). Furthermore, there are 12 or 14% errors of diction selection on dooshi and the 7 or 8% of Error are in writing and selection of kanji dooshi. Abstrak ___________________________________________________________________ Berdasarkan studi pendahuluan yang telah penulis laksanakan dengan melakukan wawancara tentang kepada pengampu mata kuliah Sakubun Chukyu Zenhan tentang kesalahan yang sering dialami oleh mahaiswa Prodi Pendidikan Bahasa Jepang UNNES dalam menulis sakubun. Selain itu, menyebarkan angket kepada 20 mahasiswa semester IV yang mengambil mata kuliah Sakubun Chukyu Zenhan. Hasilnya, 70% mahasiswa mengalami kesulitan dalam penggunaan kata kerja (dooshi).Oleh karena itu, penulis meneliti kesalahan mahasiswa dalam penggunakan dooshi pada mata kuliah Sakubun Chukyu Zenhan. Dalam penelitian ini digunakan pendekatan deskriptif kualitatif. Data pada penelitian ini adalah penggalan kalimat pada karangan mahasiswa semester IV yang dianggap kurang tepat dalam menggunakan dooshi. Adapun sumber data yang digunakan adalah karangan mahasiswa semester IV Prodi Pendidikan Bahasa Jepang Universitas Negeri Semarang. Karangan yang dijadikan sumber data berjumlah 25 karangan, diambil dari rombel 2 mata kuliah Sakubun Chukyu Zenhan dengan tema konbini no ankeeto. Hasil penelitian terdapat kesalahan dalam penggunaan dooshi sebanyak 83 kesalahan, yang terdiri atas 64 kesalahan dengan persentase 77% merupakan kesalahan pada perubahan kesalahan pada perubahan kata kerja (dooshi). Selain itu, terdapat kesalahan pemilihan diksi pada dooshi sejumlah 12 kesalahan dengan persentase 14%. Kesalahan dalam penulisan dan pemilihan kanji dooshi sejumlah 7 kesalahan dengan persentase 8%.